The whiz mob and the grenadine kid - Meloy, Colin (Balzer + Bray, an imprint of HarperCollins Publishers, 2017)
After witnessing a troupe of pickpockets pull off an incredible robbery in a busy Marseille square, Charlie Fisher agrees to protect one of the thieves if they teach him their ways, leading him into a world of adventure with global stakes.